2012
DOI: 10.1007/s00508-012-0210-5
|View full text |Cite
|
Sign up to set email alerts
|

Charakterisierung der extended spectrum b-Lactamasen (ESBL) und Bestimmung der von Kindern isolierten uropathogenen Virulenzfaktoren von Escherichia coli (E. coli) Stämmen

Abstract: Background and aim

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In the early 2000s, SHV-5 was the most common ESBL in Europe, with SHV-12 predominating in some countries [53]. Data from pediatric studies done in Croatia during this time period found that 74% (57/77) of ESBL E. coli UTI isolates carried SHV-type ESBLs (66% were SHV-5, whereas only 2.5% were CTX-M type); in Hungary, 77% (30/39) of pediatric ESBL Klebsiella clinical isolates were SHV-5-type ESBLs with the remaining isolates harboring TEM-1/SHV-12-type ESBLs [51,53]. By 2009, a study performed in a NICU in Poland showed that nearly 90% of all ESBLs were CTX-M producers, with CTX-M-3, CTX-M-15, and CTX-M-9 constituting 48.9%, 27.6%, and 12.7% of ESBLs, respectively [54].…”
Section: Europementioning
confidence: 97%
“…In the early 2000s, SHV-5 was the most common ESBL in Europe, with SHV-12 predominating in some countries [53]. Data from pediatric studies done in Croatia during this time period found that 74% (57/77) of ESBL E. coli UTI isolates carried SHV-type ESBLs (66% were SHV-5, whereas only 2.5% were CTX-M type); in Hungary, 77% (30/39) of pediatric ESBL Klebsiella clinical isolates were SHV-5-type ESBLs with the remaining isolates harboring TEM-1/SHV-12-type ESBLs [51,53]. By 2009, a study performed in a NICU in Poland showed that nearly 90% of all ESBLs were CTX-M producers, with CTX-M-3, CTX-M-15, and CTX-M-9 constituting 48.9%, 27.6%, and 12.7% of ESBLs, respectively [54].…”
Section: Europementioning
confidence: 97%
“…CTX-M-15 was the dominant type, albeit CTX-M-3 was also found in some isolates [ 43 ]. bla CTX-M genes were carried by FIA and L/M plasmids (according to the plasmid incompatibility grouping) in the early 1990s, and SHV-2 and SHV-5 were found in UTI isolates of E. coli [ 45 ]. They caused urinary tract infections in neonates and young children, and they were associated with specific virulence factors such as resistance to serum bactericidal activity and haemolysin production.…”
Section: Escherichia Colimentioning
confidence: 99%
“…Antimicrobial resistance is also on the rise in European countries that were not included in the last annual ECDC report (Table 3) [19,57,59,66,73,74]. In a recent surveillance study conducted in 42 centres in Eastern Europe, about 15% of E. coli isolates were ESBL-positive and were collected in all countries participating in this project [59].…”
Section: Epidemiology Of Resistancementioning
confidence: 99%